Besieged : stories from the Iron Druid chronicles - Hearne, Kevin (Hearne, Kevin. Iron druid chronicles, 2017)
"Atticus O'Sullivan is a Druid who has walked the earth for over 2,000 years--and had many adventures along the way. Besieged gives us a never-before-seen look into the life and back story of this popular series hero in a collection of new short stories"--